Empowerment of Women for Ukhuwah Islamiyah Through Strategies of Jam'iyah Annajah at Tanjungkarang Jati Kudus - Muzdalifah Muzdalifah (Islamic Studies Journal for Social Transformation, 2019)
This research aims to find the empowerment of women through dakwah strategy of Jamiyah Annajah at Tanjungkarang Jati Kudus. The focus of the problem is 1). Perception of women's empowerment, 2). Da'wah strategies used for fostering ukhuwah islamiyah, 3). The results of women's empowerment. Qualitative research methods by collecting data using observation, interviews, and documentation. Data analysis techniques using the model of Miles and Huberman. The results of the study showed that: 1) women's empowerment is an effort to provide opportunities for women to be able to develop their potential, abilities, and skills so that they are more advanced and utilized for the family and society at large, 2). The da'wah strategy is carried out by the Annajah jamiyah management in Tanjungkarang Jati Kudus through various activities in the education, social and economic fields. First, empowering the education sector, namely the reading of Yasin and Tahlil, al Barjanzi and Yasin Fadilah, tahtimul quran, commemoration of Islamic holidays (Maulid of the Prophet, Isro 'Mi'roj), parenting and health education, religious tourism; the second is empowerment in the social field, namely quarterly meetings for the management of jamiyah, takziyah and tahlil in the families of jamiyah members for 3 days, donors every month at the Al-Karim mosque in Tanjungkarang village, donors every month in the construction of Muslimat KB and TK Tholibin Tanjungkarang, visit members jamiyah Annajah who was sick and social services for flood victims in Tanjungkarang village in 2014; thirdly, empowerment in the economic sector, namely making calendars at the end of the year, distributing zakat fitrah to the poor and orphans once a year, and donors every month for orphan compensation. 3) The results of empowerment in the form of increasing awareness of religious knowledge for life, increasing solidarity for others namely ukhuwah islamiyah